Cokrodiharjo Karier Empu Karawitan Di Luar Tembok Karaton - Darsono Darsono (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2002)
Cokrodihardjo was born in Boyolali. His grandfather and father were puppeteers, and his mother was a gender player. He is among the best musicians and a respected gamelan teacher. His creative works become models for the court and other musicians. Cokrodihardjo had been a drummer of commercial theater (ketoprak tobong) for thirty-seven years (1931-1968), and more than twenty years he was the drummer of Ki Nyotocarita. He was also the drummer for dances and mask performances. Cokrodihardjo was noted for his rich vocabularies of drumming.